Faktor yang Mempengaruhi Penetapan Hotel X sebagai Wedding Venue - Vera Sriyani (Universitas Tarumanagara, 2022)
Wedding is one of the most important events for couples, so mostly they want their wedding event as perfect as possible. Choosing wedding venue is the first step to prepare wedding. The purpose of this research is to determine factors affect the selection of wedding venue at Hotel X. The respondent of this research is 203 prospective wedding couples who came to Hotel X. The method used in this research is multivariate analyist. This study obtained data via questionnaires and used statistical tests such as F-Test, R Square (R2)-Test, and T-Test. The result of this study shows location, atmosphere, facility, food, service and price are factors which has a significant influence on prospective wedding couple’s purchase decision.